A comparative study of low dose vaginal misoprostol and dinoprostone gel for induction of labour at term of pregnancy - Kalpana, .; Sharma, Priya; Kaushik, Amit; Rao, Priyanka; Swaroop, Neelam; Singh, Neetu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The aim of this study was to compare the low dose of vaginal misoprostol and dinoprostone gel for the induction of labour at term of pregnancy. Methods: The study was conducted on 90 women, randomized into two groups, each group having 45 women. First group received misoprostol per vaginally and second group received the dinoprostone gel. The duration of induction to delivery interval, mode of delivery and complications related to labour or foetus were recorded. Results: The mean induction to delivery interval in the misoprostol group was 11.68 ± 4.49 hours and in the dioprostone gel group was 14.85 ± 7.08 hours. Applying the modified t-test, this difference is statistically significant (P value 0.004). Thus misoprostol leads to early labour and early delivery as compared to dinoprostone gel. Conclusions: As shown in this study, vaginal misoprostol is highly effective induction agent with no adverse effect on the outcome of labour as compared to dinoprostone gel.